Zambia - Loryman, Andrew (London : Kuperard, 2018)
"A ... practical guide to Zambian culture and society ... will help you turn your visit-- whether it's for business or for pleasure-- into a memorable and enriching experience. Includes local customs and traditions; the impact of history, religion, and politics; the Zambians at home, work, and play; eating and drinking, Zambian style; dos, don'ts, and taboos; business practices; communication, spoken and unspoken; and many practical tips for managing the unexpected"--Back cover.
Includes bibliographical references (page 165) and index.
Keywords: Visitors, Foreign -- Zambia -- Life skills guides; Etiquette -- Zambia; Zambia -- Guidebooks; Zambia -- Social life and customs; Life skills guides; Guidebooks